NOUN PHRASE CONSTRUCTION IN DESCRIPTIVE WRITING BY SENIOR HIGH SCHOOL STUDENTS - Wiki Tedi Rahmawati; Hindun Lubis; Nur Widya Ningsih (FKIP Universitas Al Washliyah Medan, 2021)
This study analyzed the types of noun phrase construction. There were two problems in this study, namely the types of noun phrase construction found in writing by the first year students of senior high school and the dominant type of noun phrase constructions found in writing by the first year students of senior high school. The data in this study were taken from the students’ samples of writing particularly descriptive writing. There were two parallel classes involved which consisted of 50 students as total population and sample. This study was designed as a qualitative descriptive. The results of the analysis found that the students mostly used three types of noun phrase construction; they were Modifier + Head (M + H), Head + Modifier (H + M), and Modifier + Head + Modifier (M + H + M). As the most dominant type of noun phrase construction made by the students was the types of Modifier + Head (M + H) particularly in the arrangement of Determiner + Noun (68.03%).